Largest on earth: Discovery of a new type of fairy circle in Angola supports a termite origin. (14th December 2020) - Jürgens, Norbert; Gunter, Felicitas; Oldeland, Jens; Groengroeft, Alexander; Henschel, Joh R.; Oncken, Imke; Picker, Mike D.
Abstract : 1. Circular bare patches occur in high numbers among the vegetation of the Namib Desert margin. There is an ongoing scientific debate on the origin of these so‐called "fairy circles" (FCs). One of the most frequently discussed hypotheses regards the bare patches to be the result of localised herbivory by sand termites of the genus Psammotermes (family Rhinotermitidae). 2. In all earlier publications, the fairy circles of the Namib Desert region within their entire range from Angola through Namibia to South Africa were, in principle, regarded to be of one type, albeit increasing in size towards the north. Here we present evidence that at −16.23° latitude there is an abrupt discontinuity which separates the FCs on either side from each other. 3. South of this discontinuity all studied FCs share the properties of the previously described fairy circles in Namibia and South Africa, especially the presence of Psammotermes termites . 4. In contrast, north of −16.23°S the FCs are much larger and are caused by a different and undescribed termite species, most closely related to the harvester termite genus Microhodotermes (family Hodotermitidae). The two sets of fairy circles differ in a specific set of morphological features, associated termites, and soil parameters. 5. The observed juxtaposition of the newly discovered large structures caused by a hodotermitid termite and the Psammotermes FCs caused by a rhinotermitid species is interpreted as an interesting example of convergent evolution resulting in similar ecological structures. Abstract : The fairy circles of the Namib Desert show different morphology, north and south of 16.23° southern latitude. The giant fairy circles in the Angolan Northern Namib Desert are not caused by the sand termite Psammotermes allocerus but by an undescribed new species of the harvester termite family. The fact that two different types of Namib fairy circles are accompanied by two different termite species supports a termite origin of fairy circles.